Kejadian Bruselosis Pada Sapi Potong dan Pemetaan Wilayah Berisiko di Kabupaten Barru Provinsi Sulawesi Selatan Tahun 2015-2017 - Fitria, Nisa Nurul; Pisestyani, Herwin; Wicaksono, Ardilasunu (JURNAL KAJIAN VETERINER, 2020)
There is still lack of bruselosis in beef cattle in Barru District, South Sulawesi. The aim of this study was to analyze data about the temporary distribution of disease by measuring spreading speed, and spatial distribution by mapping risk areas for bruselosis over the past three years. The data of this study was collected using the records from Dinas Peternakan and conducting interviews using structured questionnaires. This research was a descriptive study by measuring the incidence rate and describing the risk map using geographic information system (GIS). The results of this study indicate that, based on the incidence rate, the average of distribution rate of bruselosis in beef cattle in Barru is 5 cases per 10 000 heads/year. This incidence rate always decreases every year. There was no sub-district that classified as high risk. There was one area that classified as medium risk namely sub-district of Mallusetasi. Control measure that have been carried out by goverment were successful to reduce the spread of disease.